[Hungarian Monitoring: Night of the Referendum], 27 November 1989 . Magyar rádiófigyelő: Népszavazás éjszakája, 1989. november 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. Kossuth Radio's extraordinary broadcast of November 26, 1989 covering national referendum vote count until announcement of the first partial results at dawn. László Rapcsányi's studio guests are: representatives of the larger opposition parties, constitutional lawyer Péter Schmidt, director of the Foreign Affairs Institute Péter Hardy, and two members of the National Election Committee. The program includes correspondence and local reports from the larger provincial cities, opposition parties' headquarters, the Radio Free Europe offices and the Hunters' Hall in Parliament. In the studio, party representatives evaluate the day's events and progress of the referendum based on available data, and also answer listeners' questions. A Kossuth Rádió rendkívüli adása az 1989. november 26-án tartott országos népszavazás feldolgozását közvetítette a hajnali első részeredményekig Rapcsányi László stúdióvendégei a nagyobb ellenzéki pártok képviselői, Schmidt Péter alkotmányjogász, Hardy Péter, a Külügyi Intézet Igazgatója és az OVB két tagja volt. A műsor folyamán körkapcsolásos tudósítások, helyszíni riportok hangzottak el nagyobb vidéki városokból, az ellenzéki pártok központjából, a SZER irodájából és a Parlament Vadászterméből. A stúdióban a pártok képviselői a nap eseményeit és a referendum pillanatnyi állását értékelték a rendelkezésre álló adatok alapján, ill. betelefonáló hallgatók kérdéseire válaszoltak.